2013
DOI: 10.1039/c3cc44092c
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of trisubstituted alkenes with iron porphyrin carbenes: facile synthesis of tetrasubstituted dienes and cyclopentadienes

Abstract: The unprecedented reaction of trisubstituted alkenes with iron porphyrin carbenes has been successfully developed. Both multiply substituted 1,3-butadiene and cyclopentadiene products are readily accessible with high efficiency and selectivity in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…A range of ester‐containing Cps was obtained in acceptable yields by reacting ylide‐activated, trisubstituted alkenes with substituted diazo carbonyls and catalytic amounts of tetra(4‐chlorophenyl)porphyrin iron chloride under mild conditions (Scheme B). The iron catalyst is thought to promote a formal sp 2 C−H insertion of the diazo carbonyl into the trisubstituted allylic phosphorous ylide, forming a highly reactive cyclopropylmethyl ylide intermediate, which, upon ring opening can undergo intramolecular Wittig reaction to form the respective Cp …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of ester‐containing Cps was obtained in acceptable yields by reacting ylide‐activated, trisubstituted alkenes with substituted diazo carbonyls and catalytic amounts of tetra(4‐chlorophenyl)porphyrin iron chloride under mild conditions (Scheme B). The iron catalyst is thought to promote a formal sp 2 C−H insertion of the diazo carbonyl into the trisubstituted allylic phosphorous ylide, forming a highly reactive cyclopropylmethyl ylide intermediate, which, upon ring opening can undergo intramolecular Wittig reaction to form the respective Cp …”
Section: Discussionmentioning
confidence: 99%
“…The iron catalyst is thought to promote a formal sp 2 CÀHi nsertion of the diazo carbonyl into the trisubstituted allylic phosphorous ylide, forming ah ighly reactive cyclopropylmethyl ylide intermediate, which, upon ring opening can undergo intramolecular Wittig reaction to form the respective Cp. [52] Kuninobu et al found that reacting a,b-unsaturated ketiminesa nd a,b-unsaturated carbonyl compounds in the presence of catalytic amounts of dirhenium decacarbonyl led to the formation of tetrasubstituted Cps containing at least one ester group (Scheme 15 C). In this reactiont he ketamine is thought to mediate the oxidative addition of the rheniumi nto the CÀHb ond, activating it for as ubsequenti nsertion of the a,b-unsaturated carbonyl.…”
Section: Ester-substituted Cpsmentioning
confidence: 99%
“…The addition of K 2 CO 3 to the reaction hindered the opening of the cyclopropane ring, leading to the direct formation of vinyl cyclopropanes (53) in similar yields (70–90%) . A subtle change from diazo esters to diazo ketone reagents introduced an internal carbonyl group amenable to Wittig reactions . Accordingly, its cyclopropanation with α,β-unsaturated esters (49) preceded ring opening and intramolecular Wittig reaction to form rare trisubstituted cyclopentadienes (54) in yields from 50 to 75%.…”
Section: The Dominance Of Tetrapyrrolic Macrocyclesmentioning
confidence: 99%
“…76 A subtle change from diazo esters to diazo ketone reagents introduced an internal carbonyl group amenable to Wittig reactions. 77 Accordingly, its cyclopropanation with α,β-unsaturated esters (49) preceded ring opening and intramolecular Wittig reaction to form rare trisubstituted cyclopentadienes (54) in yields from 50 to 75%.…”
Section: Cyclopropanationmentioning
confidence: 99%
“…Among reported dominor eactions, allylic ylides have been identified as versatile reactants for the preparation of carbo-and heterocyclic compounds. [5] For example, Ta ng et al have reported two domino reactions for the construction of cyclic and fused bicyclic compounds (Scheme 1a,b). [6] Furthermore, benzothiophene-fused heterocyclic compounds are important structural skeletons in biologically active compounds andm aterials [6.6.5] chemistry.…”
Section: Introductionmentioning
confidence: 99%